TROP-2, 5hmC, and IDH1 Expression in Anaplastic Thyroid Carcinoma. (June 2021) - Seok, Jae Yeon; Astvatsaturyan, Kristine; Peralta-Venturina, Mariza De; Lai, Jinping; Fan, Xuemo
Background: Anaplastic thyroid carcinoma (ATC), a highly aggressive malignancy, has no effective treatment to date. Trophoblast cell-surface antigen 2 (TROP-2), a transmembrane glycoprotein, has been suggested to be a promising novel target for sacituzumab govitecan, an antibody-drug conjugate. 5-Hydroxymethylcytosine (5hmC) has a role in tumor suppression and promoting modification. Additionally, isocitrate dehydrogenase 1 (IDH1) mutations are strongly associated with increased overall survival in gliomas and worse prognosis in leukemias. This study attempts to evaluate the immunoexpression of TROP-2, 5hmC, and IDH1 in ATCs and to determine their potential impact in targeted therapy. Methods: Twenty-four ATCs were retrieved, with 9 cases that occurred de novo and 15 cases derived from either papillary thyroid carcinoma (PTC) or follicular thyroid carcinoma (FTC). Sections were immunostained with TROP-2, 5hmC, and IDH1 antibodies, and evaluated using the QuPath program. The t tests were performed using SPSS software. Results: TROP-2 was detected in 12 ATCs with 9 cases demonstrating a high expression and in all PTC components, and absent in all FTC components of secondary ATCs. 5hmC expression was moderately reduced in PTC and FTC components and markedly reduced in ATC. The entire cohort showed a total absence of IDH1. Conclusions: Increased TROP-2 immunoexpression in some ATCs supports that these patients may potentially benefit from an antibody-drug conjugate therapy targeting TROP-2. Markedly reduced 5hmC expression suggests that 5hmC may be used as potential therapeutic targets for ATC. The total lack of IDH1 R132H mutation by immunostain indicates that it has no prognostic and therapeutic value in ATC.